Energy efficiency and productivity of a Pressure Swing Adsorption plant to purify bioethanol: Disturbance attenuation through geometric control - Jesse Y. Rumbo-Morales; Gerardo Ortiz-Torres; Felipe D.J. Sorcia-Vázquez; Carlos Alberto Torres-Cantero; Jair Gómez Radilla; Mario Martínez García; Julio César Rodríguez-Cerda; Antonio Márquez Rosales; Moises Ramos-Martinez; Juan Carlos Mixteco-Sánchez; Mayra G. Mena-Enriquez; Mario A. Juarez (Digital Chemical Engineering)
Biofuels produced from renewable raw materials, in this case bioethanol, provide a sustainable and renewable energy source for the future, as bioethanol positively impacts the economy, the environment, and society. Bioethanol is an alternative and immediate solution to mitigate the main greenhouse gases generated by transportation and industries that use fossil fuels. However, to produce bioethanol it is necessary to use advanced dehydration processes or technologies. Currently, azeotropic distillation, extractive distillation, and the Pressure Swing Adsorption (PSA) process using selective zeolites on water molecules are used. This PSA process has shown high selectivity, high yield, and high energy efficiency for producing anhydrous ethanol compared to other technologies. This work aims to implement automatic control laws (geometric and PID) to maintain stable the desired purity (99.5%), have higher bioethanol recovery and generate higher productivity using less energy. Both controllers performed adequately on the PSA bioethanol-producing plant, however, the geometric control presented greater robustness against disturbances, achieving to maintain stable bioethanol purity above 99% by wt, generating a recovery of 73.62%, with productivity of 59.07 kmol and using an energy efficiency of 59.21%. Using this control law, it was possible to use the entire length of the columns to adsorb a greater amount of water molecules and achieve higher production.